(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Forest plant seeds can be in the form of generative or vegetative used to breed forest plants. Sources of seeds come from stands inside and outside the forest area to produce quality seeds. The availability of quality forest plant seeds is still limited. The Faculty of Forestry, Winaya Mukti University, is interested in providing community service to partners in the form of training and certification of expertise in determining the quality of forest plant seeds to prepare group members with a nationally recognized BNSP certificate. This community service (PKM) has three partner groups: the Jingkang Village group, Tanjungmedar District, Sumedang Regency, Loa Village Group, Paseh District, and Bandung Regency Forest Village Community Institution (LMDH) Cempaka Bentang and Laksana Village, Ibun District, Kabupaten Bandung. Bandung called the Forest Farmers Group (KTH) Kamojang. The method begins with training on seed handling and quality inspection of forest plant seeds which includes how to take seed samples, analyze seed purity, determine the weight of a thousand grains, determine water content, and test germination. Skill competency certification activities refer to the International Seed Testing Association (ISTA). The seeds used are Sengon, Gmelina, Suren, and Trembesi seeds. All partner groups welcome this activity and hope that this activity can continue to improve the knowledge and skills of participants in supporting superior human resources and forestry professionals to support the community’s economy.